2011
DOI: 10.1097/mpa.0b013e31821396b2
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Low Bone Mineral Density in Patients With Tropical Calcific Pancreatitis

Abstract: Despite their young age, patients with TCP have significantly low BMD. Measures to improve nutrition should be instituted in all TCP patients from an early age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
2
9
1
Order By: Relevance
“…16 In a cross-sectional study, Joshi et al studied 72 patients with tropical chronic pancreatitis (TCP) and found that their lumbar spine and total hip BMD were significantly lower than that in the controls. 10 They also found that vitamin D deficiency was equally prevalent among patients (86%) and controls (85%).However, we did not find any statistically significant correlation between chronic pancreatitis severity based on the Cambridge Criteria and the average spinal and femoral T-scores in our patients. There was also no significant difference in the number of patients with osteoporosis and osteopenia across different Cambridge groups.…”
contrasting
confidence: 43%
See 4 more Smart Citations
“…16 In a cross-sectional study, Joshi et al studied 72 patients with tropical chronic pancreatitis (TCP) and found that their lumbar spine and total hip BMD were significantly lower than that in the controls. 10 They also found that vitamin D deficiency was equally prevalent among patients (86%) and controls (85%).However, we did not find any statistically significant correlation between chronic pancreatitis severity based on the Cambridge Criteria and the average spinal and femoral T-scores in our patients. There was also no significant difference in the number of patients with osteoporosis and osteopenia across different Cambridge groups.…”
contrasting
confidence: 43%
“…[7][8][9] Moreover, majority of these studies have enrolled patients with ACP and very few studies have examined BMD in ICP patients. 4,10 All these studies have shown that BMD is reduced significantly in patients with chronic pancreatitis and these patients are at increased risk of bone fractures.Our study corroborates that nearly two-thirds of our chronic pancreatitis patients had metabolic bone disease and these patients are at increased risk of bone fractures. Dujsikova et al studied 73 patients (17 females and 56 males)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations